2012
DOI: 10.1063/1.4756997
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric vs. structural properties of large-distance sputtered epitaxial LSMO/PZT heterostructures

Abstract: We report on large-distance rf-magnetron sputtering as a competitive alternative to pulsed laser deposition and off-axis sputtering for the growth of epitaxial PbZr0.52Ti0.48O3 (PZT) thin films. To determine the characteristics of the PZT films, the studies were focused on the interplay between microstructural and ferroelectric properties. The films were deposited on insulating or conducting (Nb-doped) SrTiO3 and MgO substrates with La0.83Sr0.17MnO3 as bottom electrode. The uniformity and homogeneity of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A fundamental parameter of a ferroelectric is the absolute remanent polarization (P r ), which can be measured from the P-E loops by subtracting parasitic contributions such as linear capacitances and leakage currents. 34 Well-saturated P-E loops were observed for PZTNi30 films of different thickness at room temperature, shown in Fig. 5(a).…”
Section: B Electrical Characterizationmentioning
confidence: 93%
“…A fundamental parameter of a ferroelectric is the absolute remanent polarization (P r ), which can be measured from the P-E loops by subtracting parasitic contributions such as linear capacitances and leakage currents. 34 Well-saturated P-E loops were observed for PZTNi30 films of different thickness at room temperature, shown in Fig. 5(a).…”
Section: B Electrical Characterizationmentioning
confidence: 93%
“…19,21,25 The impact of the total film thickness on the ferroelectric properties was not investigated due to issues related to short-circuiting the capacitor structure during sputter deposition of the Au top electrodes (for thinner films) and voltage limitations (±12 V) of the ferroelectric testing system (for thicker films). Panel (a) of Figure 5 shows a typical polarization-electric field (P-E) hysteresis loop at 400 Hz switching frequency; the measured polarization switching currents are also shown, for clarity.…”
Section: Resultsmentioning
confidence: 99%
“…17 Research over the past several decades has demonstrated that the ferroelectric behavior of PZT thin films can be strongly affected by the choice of the top and bottom electrodes, the Zr/Ti ratio, and by the deposition method used. 18,19 However, the microstructure, texture, film thickness, and other parameters also have significant effects on the electrical polarization properties. [20][21][22] Among other things, it has been shown that the use of La 1-y Sr y MnO 3 /SrTiO 3 :Nb heterostructure substrates -referred to as LSMO/STO:Nb in the following -instead of bare STO:Nb single crystal substrates as back electrodes is beneficial for preventing polarization loss due to leakage.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, FE oxides are renowned for their ability to retain a spontaneous electric polarization upon application and subsequent removal of an external voltage 19–23. The control of the switchable FE polarization opens the opportunity to implement FE field‐effect transistors24 and memcapacitors16 with promising features to be used in artificial synaptic circuits.…”
Section: Figurementioning
confidence: 99%
“…Which of the two processes predominates depends to a large extent on the structural features of the considered FE oxide. Indeed, FE devices based on the purely electrostatic preservation of charge carriers require a high crystalline quality with a low amount of structural defects in order to avoid the onset of leakage currents 23,25,26. On the contrary, a common approach to realize resistive switching in FE memristors is to exploit the formation of preferential conducting paths due to the presence of structural defects 1,27.…”
Section: Figurementioning
confidence: 99%